Desafios e propostas para a evangelização da juventude na cidade de São Paulo - Sá, Nei Márcio Oliveira de (2010)
This research has the objective to reflect on the youth evangelization in the city of São Paulo, presenting the main questions that involve their reality in the megalopolis and the challenges to make a broad pastoral work in the current society. The reflection on this theme is essential because, nowadays, many parents, educators and pastoral agents are taken aback by the difficulty in establishing an evangelizing dialog with adolescents and young people and in understanding their world, habits, values and needs. Besides, the work done with the youth is the basis to the development of the society and of the institutions, including the church. Making use of the method See-Judge-Act and counting on the support of the varied bibliography, One starts from the anthropological and psychosocial aspects of the youth, realizing the conceptual analysis of the main terms that are utilized in its discrimination and analyzing its presence in the complex dynamics of work of the megalopolis. There are many realities of youth in the city, which need specific answers and request new pastoral strategies, differed and concomitant. Counting on the contribution of the theological reflection, based on the Scriptures, on the Teaching of the Church and on the indications done by the main current pastoral documents and plans, in this Dissertation the work done in the current context is evaluated and many proposals of actions to an effective evangelizing action of the youth in the city of Sao Paulo are presented